2004
DOI: 10.4049/jimmunol.172.11.6658
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of an Immunodominant CD4+ T Cell Epitope in Human IFN-β Does Not Result in an In Vivo Response Directed at the Subdominant Epitope

Abstract: The BALB/cByJ mouse strain displays an immunodominant T cell response directed at the same CD4+ T cell epitope peptide region in human IFN-β, as detected in a human population-based assay. BALB/cByJ mice also recognize a second region of the protein with a lesser magnitude proliferative response. Critical residue testing of the immunodominant peptide showed that both BALB/cByJ mice and the human population response were dependent on an isoleucine residue at position 129. A variant IFN-β molecule was constructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 42 publications
2
46
0
1
Order By: Relevance
“…The explanation for this latter observation is not clear, but it was suggested that for some subdominant epitopes the efficient priming of responses depends on the establishment of a productive proliferative response to the immunodominant epitope (31).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The explanation for this latter observation is not clear, but it was suggested that for some subdominant epitopes the efficient priming of responses depends on the establishment of a productive proliferative response to the immunodominant epitope (31).…”
Section: Discussionmentioning
confidence: 98%
“…2). No IFN-␥ release was found in response to the control peptide (ESAT-6 [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] ). In addition to the immunodominant P1 (ESAT-6 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] ) epitope, the analysis of peptides covering the full sequence of ESAT-6 revealed two additional subdominant epitopes to which T cells are not primed during the natural infection.…”
Section: Identification Of Subdominant Epitopes In Esat-6mentioning
confidence: 99%
“…However, the identification and removal of B-cell epitopes is exceedingly difficult given their conformational nature, and is further complicated by our incomplete knowledge of naive antibody repertoires, and how they vary across different human populations. In contrast, there is extensive evidence from animal models, in vitro experiments, and early stage clinical studies, that the disruption of T-cell epitopes can reduce antibody responses in some therapeutic proteins (13,14). T-cell receptors on CD4þ T cells recognize antigenic peptides (typically 13-25mers) presented in complex with MHC-II molecules on the surface of antigen-presenting cells (APCs).…”
mentioning
confidence: 99%
“…Therefore, many attempts have been made to diminish the immunogenicity of immunotoxins by humanization/de-immunization of the antibody binding domains (14,15), modification with macromolecules (16)(17)(18)(19), or structural changes of the PE domain (20)(21)(22). Several preclinical studies described that deletions or mutations within the PE toxin domain led to the removal of immunodominant Band T-cell epitopes and successfully contributed to diminished immunogenicity and reduced ADA production (20)(21)(22).…”
mentioning
confidence: 99%